Yield and nutritional evaluation of the banana hybrid 'FHIA-18' as influenced by phosphate fertilization - Bolfarini, Ana Carolina Batista [UNESP]; Putti, Fernando Ferrari [UNESP]; Souza, Jackson Mirellys Azevedo [UNESP]; Silva, Marcelo de Souza [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP] (Taylor & Francis Inc, 2020)
The 'FHIA-18' hybrid banana is an alternative for producers as it is resistant to Black Sigatoka and Panama disease. However, few studies report the nutritional requirement of this hybrid, especially phosphorus. It is known that the efficiency of phosphorus use can be improved, reducing the need for application, depending on the genotype cultivated. Therefore, this study aimed to evaluate the yield and mineral nutrition of 'FHIA-18' hybrid banana on phosphate fertilization. A banana orchard with the cultivar 'FHIA-18' was conducted on a Typical Red Latosol. Then, triple superphosphate fertilizer was applied on plants at 0, 20, 30, 40, 50, and 60 kg ha(-1) year(-1), over three productive seasons. At the time of flowering the macro and micronutrient contents of the leaves were evaluated. Subsequently, the nutrient contents of the fruits were evaluated. For this, fruit pulp samples from the third and fourth hands were collected. In addition, yield was estimated considering cluster mass and plant density. The following dose 36 kg ha(-1) of P2O5 year(-1) increased the content of phosphorus in the leaf, despite that banana hybrid cultivar FHIA 18 demanded 50% of the recommended fertilizer to achieve its maximum yield (29.4 t ha(-1) year(-1)). Phosphate fertilization promoted significant changes in P, Ca, Cu, and Zn contents of leaves and fruits. Therefore, it is concluded that the mineral nutrition of banana 'FHIA-18' is affected by phosphate fertilization, as well as requiring less P than recommended to achieve higher yield.
Keywords: Mineral nutrition; Musa spp; P2O5; triple superphosphate